2022
DOI: 10.1152/ajpheart.00467.2022
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian hormones do not mediate protection against pulmonary hypertension and right ventricular remodeling in female mice exposed to chronic, inhaled nicotine

Abstract: Electronic cigarette use has increased globally prompting calls for improved understanding of nicotine's cardiovascular health effects. Our group has previously demonstrated that chronic, inhaled nicotine induces pulmonary hypertension and right ventricular (RV) remodeling in male mice, but not female mice, suggesting sex differences in nicotine-related pathology. Clinically, biological females develop pulmonary hypertension more often, but have less severe disease than biological males, likely due to the card… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 29 publications
0
0
0
Order By: Relevance
“…E-cigarette vapor exposure in mice also results in airway inflammation and an impaired immune response to bacteria and viruses, including defective bacterial phagocytosis [101]. To evaluate female-specific effects, a study using intact and ovariectomized female mice exposed to nicotine for 3 months revealed no differences in serum cotinine levels and no structural or functional cardiopulmonary dysfunction changes [106].…”
Section: Central Nervous Systemmentioning
confidence: 99%
“…E-cigarette vapor exposure in mice also results in airway inflammation and an impaired immune response to bacteria and viruses, including defective bacterial phagocytosis [101]. To evaluate female-specific effects, a study using intact and ovariectomized female mice exposed to nicotine for 3 months revealed no differences in serum cotinine levels and no structural or functional cardiopulmonary dysfunction changes [106].…”
Section: Central Nervous Systemmentioning
confidence: 99%